Analysis Of The Influence Crm Dimensions On Employee-Based Brand Equity - Wisnu Fiskal Saputro; Puspitaloka Mahadewi, Erlina (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Indonesia is rapidly experiencing in last 5 years with transition from conventional to online transportation with the emergence of various well-known online applications such as Grab. To remain competitive, branding and customer relationship management are important marketing strategies for a company. This research aimed to examine the influence of CRM dimensions on employee-based brand equity among Grab online motorcycle taxi drivers in Jabodetabek. The methodology using quantitative study was built on previous research, with deductive and used a quantitative mono method where respondents were asked to rate each item according to a 1 to 5 likert scale. The number of respondents in this study required 210 respondents who had worked as Grab drivers for 1 year or more and made it their main profession. The research used multiple linear regression methodology to test the hypothesis with 4 independent variables: customer orientation, knowledge management, CRM organization and technology-based CRM which influence the dependent variable, namely employee-based brand equity. The result findings showed that all the hypotheses developed had been successfully proven, the dimensions of CRM had a positive effect, both partially and simultaneously, on employee-based brand equity. These results added to the literature on this topic and verified the importance of customer relationship management dimensions in influencing employee-based brand equity.